Optimal Inflationary and Reserve Requirement Policies: A Study of an Economy with an Informal Sector - Ali, Hamid E. (Universiti Utara Malaysia, 2011)
Governments in developing economies often resort to taxing bank money balances through imposition of high reserve requirements and also by relying on seigniorage to finance their deficits. In the context of those practices, this research attempts to answer the following questions. First, why do developing economies with an informal sector resort to inflationary measures to finance their activities? Second, how does a government induce an agent to choose the formal economy? As to the first question on the trade-off between inflation and reserve requirements, it is shown that of maximum inflation and minimum reserve requirements will increase the steady-state utility of an optimizing agent. Regarding the second question, the agents prefer the informal economy if policy relies on a maximum reserve requirement.